Numerical study of fluid flow and heat transfer for flow of Cu-Al2O3-water hybrid nanofluid in a microchannel heat sink. (2022) - Murali Krishna, V.; Sandeep Kumar, M.; Muthalagu, R.; Senthil Kumar, P.; Mounika, R.
Abstract: The use of micro-electronic devices in many applications such as aerospace, telecommunications, micro-electronics, robotics is drastically increasing and they need efficient cooling system. Micro-channel heat sinks (MCHS) are getting significant importance due to their very high surface to volume ratio and high heat dissipation rate. The hybrid nanofluids playing a vital role as cooling fluids in various thermal transportation applications due to their extraordinary heat transport characteristics. A numerical study is taken up for laminar flow of hybrid nanofluid as a heat transport medium in a rectangular MCHS to realize thermal and hydrodynamic behaviour in forced convection. The influence of Reynolds number (Re) and volume concentration of nanoparticles in Cu-Al2 O3 /water hybrid nanofluid on MCHS performance is investigated in the present paper. The correlations presented in the literature are used to calculate the properties of hybrid nanofluids. For various mixture ratios of 25–75%, 50–50% and 75–25% hybrid nanofluids the heat transport rate and pressure drop are calculated at different Reynolds numbers and compared with mono nanofluids of Cu-water (H2 O) and Al2 O3 -water. An enhancement in heat transfer rate is observed with raise in volume fraction and marginal increase in pressure drop is observed for hybrid nanofluids over mono nanofluids of Cu-water and Al2 O3 -water. The results indicate an increase of 13.2% and 23.07% in Nusselt number for Cu-Al2 O3 /water hybrid nanofluid compared with Cu/water and Al2 O3 /water mono nanofluids respectively at 2.5% volume fraction. It is found from the numerical results that the pumping power requirement is less for hybrid Cu-Al2 O3 /water nanofluid compared to Cu/water nanofluids and an increase of 430 Pa compared to pure water. The data existing for Al2 O3 -water nanofluid in the literature is used to validate the present model.